2005
DOI: 10.2214/ajr.185.3.01850689
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Virtual Cystoscopy, Multiplanar Reformation, and Source CT Images with Contrast Material-Filled Bladder for Detecting Lesions

Abstract: Virtual cystoscopy is more accurate than multiplanar reconstruction and source CT images for the detection of lesions in the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…Therefore, a virtual cystoscopic rendering of the bladder takes a short time to navigate and does not require great skill on the part of the operator (4)(5)(6)18). On the other hand, according to a study by Kim et al, virtual cystoscopy was found superior than multiplanar reconstruction and source CT images for lesion detection in the contrast material-filled bladder (22). However, most stud- sidering conventional cystoscopy to be the gold standard, we found the following diagnostic values for the identification of bladder lesions on virtual cystoscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a virtual cystoscopic rendering of the bladder takes a short time to navigate and does not require great skill on the part of the operator (4)(5)(6)18). On the other hand, according to a study by Kim et al, virtual cystoscopy was found superior than multiplanar reconstruction and source CT images for lesion detection in the contrast material-filled bladder (22). However, most stud- sidering conventional cystoscopy to be the gold standard, we found the following diagnostic values for the identification of bladder lesions on virtual cystoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, there is no need for examination in prone and supine position. Therefore, this means lesser radiation and cost (3,22). However, urine and contrast could not be mixed properly with this method for virtual cystoscopy.…”
Section: Commentsmentioning
confidence: 99%
“…Our findings are also consistent with previous reports. For example, Nerumi et al [22] identified only 70% of lesions <1 cm by using a single-detector-row scanner with 3-mm collimation, and Kim et al [23] identified 82% of lesions <5 mm using a four-detector-row scanner and 1.25-mm collimation. In contrast, in a study conducted with a 16-detector-row scanner and 3-mm collimation, Song et al [18] defined CTC with VC an unreliable technique for detecting lesions <5 mm (only 60% of lesions detected).…”
Section: Discussionementioning
confidence: 99%
“…Virtual cystoscopy, obtained by manipulating CTU data acquired through the contrast-filled bladder during the excretory phase, allows navigation within a 3-dimensional model and has shown promise for detecting bladder mucosal lesions [26].…”
Section: Reviewmentioning
confidence: 99%